Nutrient Optimization for Vegetable Production Under Decoupled Aquaponics Using Brackish Water - Abdelfattah, Salma Walid Hany Ahmed (AUC Knowledge Fountain, 2023)
As the world moves to more sustainable agriculture methods in the agribusiness industry, decoupled aquaponics is recognized as one of the newest techniques currently being utilized to achieve more local food security. As the topic is still freshly new within the industry, a finite number of publications and studies have been made that address the topic hands-on with its many variables. Subsequently, in this paper, an experiment was conducted to assess the most optimized production conditions of both lacinato kale (Brassica oleracea var.palmifolia) and Swiss chard Bright Light (Beta vulgaris ssp. Cicla var. flavescens) plants through the utilization of a decoupled aquaponic system using a drip hydroponic setup and control group, evaluating the variability of effluent to inorganic fertilizer ratio addition to the plants. Consequently, the results have shown the best potential to be anticipated from the Swiss Chard cultivation across both Treatment 3, the 50:50 effluent to inorganic fertilizer and Treatment 4, the 25:75 effluent to inorganic fertilizer ratio, in consideration of the nine growth parameters of leaf number, plant height, chlorophyll count, leaf area, fresh and dry weights, nitrogen and protein content alongside the support of the economic study. On the other hand, although the control group had outweighed the kale different treatment results, Treatment 4 with a 25:75 effluent to inorganic fertilizer ratio, had been significantly indifferent in many of the nine growth parameters and has been shown upon after the economic study had prevailed the much higher economic feasibility of than that of the control. However, further assessment of varying effluent to inorganic fertilizer ratios would be needed to validate a variety of other ratios that are to be assessed.